2004
DOI: 10.1074/jbc.m314302200
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol is a Peroxidase-mediated Inactivator of COX-1 but Not COX-2

Abstract: Resveratrol (3,4 ,5-trihydroxy-trans-stilbene) is a phytoalexin found in grapes that has anti-inflammatory, cardiovascular protective, and cancer chemopreventive properties. It has been shown to target prostaglandin H 2 synthase (COX)-1 and COX-2, which catalyze the first committed step in the synthesis of prostaglandins via sequential cyclooxygenase and peroxidase reactions. Resveratrol discriminates between both COX isoforms. It is a potent inhibitor of both catalytic activities of COX-1, the desired drug ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(97 citation statements)
references
References 36 publications
4
88
0
5
Order By: Relevance
“…In fact, resveratrol noncompetitively inhibits the cyclooxygenase activity of COX-1 [100]. A recent study has shown that resveratrol-inactivated COX-1 was devoid of both cyclooxygenase and peroxidase activities, this inactivation being accompanied by a concomitant oxidation of resveratrol [101]. Moreover, docking studies on both COX-1 and COX-2 protein structures also revealed that hydroxylated but not methoxylated resveratrol analogues are able to bind to the previously identified binding sites of the enzymes [102].…”
Section: C) Resveratrol Chemoprevention By Inhibition Of Lipid Mediatorsmentioning
confidence: 92%
“…In fact, resveratrol noncompetitively inhibits the cyclooxygenase activity of COX-1 [100]. A recent study has shown that resveratrol-inactivated COX-1 was devoid of both cyclooxygenase and peroxidase activities, this inactivation being accompanied by a concomitant oxidation of resveratrol [101]. Moreover, docking studies on both COX-1 and COX-2 protein structures also revealed that hydroxylated but not methoxylated resveratrol analogues are able to bind to the previously identified binding sites of the enzymes [102].…”
Section: C) Resveratrol Chemoprevention By Inhibition Of Lipid Mediatorsmentioning
confidence: 92%
“…Importantly, recent studies revealed that resveratrol effectively inhibits aggregation of platelets from patients with aspirin resistance (Stef and Veress, unpublished data, 2005). Structure-activity relationships on methoxy-resveratrol analogs showed that the m-hydroquinone moiety is essential for irreversible inactivation of cyclooxygenase-1 [38]. These findings encourage the search for structurally related compounds with better bioavailability for cardiovascular protection in elderly patients with aspirin resistance.…”
Section: Anti-platelet Action Of Resveratrolmentioning
confidence: 98%
“…2) and it has been suggested that this action may be responsible for its protection against coronary heart disease [ [33][34][35][36][37]. Resveratrol was shown to inhibit cyclooxygenase-1 [38], which likely contributes to its aspirin-like effects. Other potential mechanisms of the antiplatelet action of resveratrol involves inhibition of signal transduction pathways including MAP kinases [33] and polyphosphoinositide signaling [37].…”
Section: Anti-platelet Action Of Resveratrolmentioning
confidence: 99%
“…In addition, resveratrol inhibits O 2 . production by NADPH oxidase-2 (15), blocks cyclooxygenase activity (42), and thus, might protect DNA against mutations induced by reactive oxygen species (see Scheme 1). To test whether resveratrol inhibits HOCl-triggered DNA oxidation, we measured the ability of resveratrol to block DNA-DMPO nitrone adduct formation and luminol oxidation by HOCl.…”
Section: Discussionmentioning
confidence: 99%